インプラント体周囲の移植歯肉のクリーピング現象 - 伊藤, 幸司; 前田, 初彦; 亀山, 洋一郎; 堀田, 康記; 小松, 晋一 (Journal of Japanese Society of Oral Implantology, 2001)
Creeping of grafted gingiva can occur after free gingival grafting to the region surrounding natural teeth. To our knowledge, however, creeping of grafted gingiva after placement of a free gingival graft around implants has not been reported previously. We describe creeping of a free gingival graft placed around implants. The creeping gingiva covered the gap between the superstructures and three implants. The histopathological findings of the these regions are also described. In December 1993, three ITI-Bonefit implants were placed, using GTAM membrane with the GBR method, at a defect in the right mandibular molar region. Subsequently, a free gingival graft was placed around the three implants, to obtain cornified immobile mucosa. An operator-removable superstructure (ITI Octa-System) was used. Clinically, creeplng of the cornified gingiva surrounding the implants was gradually noted about 1 year after the surgery. After 4 years, the gingiva covered the gap at the junction between the implants and supersturucture. After 5 years, a specimen was taken from tissue surrounding the implants associated with gingival creeping for histopathological examination. The examination revealed normal epithelial tissue. Beneath the epithelium, there was fibrous connective tissue thickening. There was no inflammatory cell infiltration. At the region where the creeping gingival graft extended beyond the gap between implants and superstructure, there was no deep proliferation of epithelial tissue along the implant surface. Nearly normal gingiva covered the gap, and fibrous connective tissue thickening was seen beneath the epithelium. These findings suggest that a free gingival graft around impiants is very useful.